Investigation of the structural and thermal properties of Y, Ag and Ce-assisted SiO2-Na2O-CaO-P2O5-based glasses derived by sol-gel method - Kaygili, Omer; Keser, Serhat; Tatar, Cengiz; Koytepe, Suleyman; Ates, Tankut (Springer, 2017)
A glass with the composition of the SiO2-Na2O-CaO-P2O5 was synthesized by sol-gel method at temperature of 900 A degrees C, and then yttrium-, silver- and cerium-containing glasses were prepared at the same conditions using this base system. The structural and thermal properties of the glass samples were investigated by X-ray diffraction, Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy, energy-dispersive X-ray (EDX) spectroscopy and differential thermal analysis techniques. The Ca-5(PO4)(2)(SiO4)(6) phase having the orthorhombic crystal system is detected for each sample without any secondary phase, and this phase is confirmed by the FTIR spectra. With the addition of Y, Ag and Ce to the SiO2-Na2O-CaO-P2O5 system, the variations in the average crystallite size, crystallinity percent, lattice parameters and unit cell volume are observed. A decrease in the crystallization peak temperature and the changes in the glass transition temperature are seen with the addition of Y, Ag and Ce to the base system. The addition of Y, Ag and Ce to the base glass increases significantly its density. The EDX spectra of the as-prepared samples verify the introduction of the as-mentioned elements.
Keywords: Glass; Sol-gel; Crystal structure; Differential thermal analysis; Morphology